Innovation in Merdeka Curriculum E-Module: Integrating Scientific Approach with Socio-Scientific Issues to Improve Students' Critical Thinking - Rohali, Amelia; Hamimi, Erti (Universitas Pendidikan Ganesha, 2024)
The critical thinking skills of students in Indonesia remain below average, presenting a significant challenge in preparing students to meet the demands of the 21st century. This study aims to develop an independent curriculum e-module integrating the scientific approach with Socio-Scientific Issues (SSI) to enhance critical thinking skills. The development process employs the ADDIE model, encompassing five stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved seventh-grade students studying biodiversity. Qualitative data were collected through teacher interviews and questionnaires, while quantitative data were obtained from validator scores, teacher and student evaluations, as well as pre-test and post-test results. Data analysis included qualitative descriptive techniques, percentage analysis, validity and reliability tests, normality tests, homogeneity tests, t-tests, and N-Gain tests. The validation results for media and materials reached 93.75% and 98.21%, respectively. Practicality assessments by teachers and students achieved 95.97% and 87.44%, respectively. The N-Gain test demonstrated moderate improvements across five critical thinking indicators. It can be concluded that the e-module is valid, practical, and effective for use in teaching and learning.